Fast, automated, real‐time 3D passive balloon catheter tracking during MRI‐guided cardiac catheterization using orthogonal projection imaging and real‐time image‐based catheter detection - Kowalik, Grzegorz T.; Kerfoot, Eric; Kunze, Karl; Neji, Radhouene; Moon, Tracy; Mellor, Nina; Razavi, Reza; Pushparajah, Kuberan; Roujol, Sébastien (Magnetic resonance in medicine, 2025)
Purpose MRI‐guidance of cardiac catheterization is currently performed using one or multiple 2D imaging planes, which may be suboptimal for catheter navigation, especially in patients with complex anatomies. The purpose of the work was to develop a robust real‐time 3D catheter tracking method and 3D visualization strategy for improved MRI‐guidance of cardiac catheterization procedures. Methods A fast 3D tracking technique was developed using continuous acquisition of two orthogonal 2D‐projection images. Each projection corresponds to a gradient echo stack of slices with only the central k‐space lines being collected for each slice. To enhance catheter contrast, a saturation pulse is added ahead of the projection pair. An offline image processing algorithm was developed to identify the 2D coordinates of the balloon in each projection image and to estimate its corresponding 3D coordinates. Post‐processing includes background signal suppression using an atlas of background 2D‐projection images. 3D visualization of the catheter and anatomy is proposed using three live sagittal, coronal, and axial (MPR) views and 3D rendering. The technique was tested in a subset of a catheterization step in three patients undergoing MRI‐guided cardiac catheterization using a passive balloon catheter. Results The extraction of the catheter balloon 3D coordinates was successful in all patients and for the majority of time‐points (accuracy >96%). This tracking method enabled a novel 3D visualization strategy for passive balloon catheter, providing enhanced anatomical context during catheter navigation. Conclusion The proposed tracking strategy shows promise for robust tracking of passive balloon catheter and may enable enhanced visualization during MRI‐guided cardiac catheterization.